Development and clinical validation of a novel photography‐based skin pigmentation evaluation system: a comparison with the calculated consensus of dermatologists. (1st February 2016) - Cho, M.; Lee, D.‐H.; Kim, Y.; Koh, W.; Chung, J. H.; Kim, H. C.; Kim, S.
Abstract: Objective: Various cosmetics, medicines, and light and laser treatments have been increasingly developed to improve pigmentary skin alterations such as melasma, actinic lentigo and dyschromia. To determine the efficacy of these modalities in view of the changes in pigmentation, an objective and reliable device that has a comparable performance to that of physicians is required. We developed a novel photography‐based skin pigmentation evaluation system and validated its accuracy and reliability with a newly proposed method. Methods: A novel photography‐based system was developed that integrates a consistent photography setting and image processing diagnostic algorithms. To automatically detect areas of pigmentation, the diagnostic algorithms were applied to photographs, which were obtained from 31 female patients. To validate its performance in comparison with the physicians' evaluation, five dermatologists independently evaluated the area of pigmentation. The clinical consensus area of pigmentation (CCAP) was calculated based on the consensus of five dermatologists' to exclude subjectivity or bias, and it was compared with the pigmentation area determined by the system. Results: Forty‐four photographs with pigmented areas were evaluated by the system and the physicians. In contrast to the individual physician assessments, CCAP reduced the error that occurred due to subjectivity and bias, particularly for areas with indistinct pigmentation, and it was set as the gold standard. The results from the system showed a mean accuracy of 92.1% and a standard deviation of 4.6% in comparison with CCAP. Conclusion: This pigmentation evaluation system can reproduce the physicians' consensus, suggesting that this system can support the dermatologists' objective evaluation of pigmentation.